Changes in the Treatment and Prevention of Heart Failure Based on the 2023 Focused Update of the 2021 European Society of Cardiology Guidelines - Skotnicka, Joanna; Błaszczak, Karolina; Witkowska, Maria; Turek, Monika; Witkowski, Maciej; Ślósarz, Tymoteusz; Krupa, Paulina; Kaczorowski, Rafal; Forenc, Tomasz; Wojciechowska, Klara (Quality in Sport, 2024)
Introduction and Objective: The 2023 update to the 2021 ESC Guidelines for diagnosing and treating acute and chronic heart failure introduces significant changes in pharmacotherapy and prevention. Staying informed about these updates is crucial given the evolving landscape of heart failure management. This review provides an overview of the latest recommendations and supporting evidence. Review Methods: A comprehensive review of scientific publications and guidelines from PubMed, Google Scholar, Clinical Key, Via Medica Journals, and relevant clinical guidelines was conducted to ensure the most recent evidence is considered. Brief Description of the State of Knowledge: Heart failure is a growing global concern. The 2023 update highlights key management changes. Recent trials, including EMPEROR-Preserved and DELIVER, show empagliflozin and dapagliflozin reduce heart failure hospitalization and cardiovascular death in patients with mildly reduced and preserved ejection fraction. The guidelines now recommend intravenous iron for patients with reduced or mildly reduced ejection fraction and iron deficiency. For those with type 2 diabetes and chronic kidney disease, SGLT2 inhibitors and finerenone, a non-steroidal mineralocorticoid antagonist, are recommended to reduce heart failure hospitalization and prevent renal function decline. Summary: The 2023 ESC Guidelines update offers revised recommendations for heart failure management and prevention, integrating the latest clinical trial data and meta-analyses. Key areas include the use of SGLT2 inhibitors, iron deficiency management, and preventive strategies for high-risk populations. Implementing these guidelines can significantly improve preventive and therapeutic outcomes for heart failure patients.